Collaborative Governance dalam Pengembangan Usaha Mikro Kecil Menengah (UMKM) di Kecamatan Kedungbanteng Kabupaten Banyumas: Collaborative Governance in the Development of Micro, Small and Medium Enterprises (MSMEs) in Kedungbanteng District, Banyumas Regency - Elani, Khafni Arij; Pribadi, Indah Ayu Permana; Sutikno, Chamid; Amanda, Ariesta; Atika, Zaula Rizqi (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research analyzes the implementation of Collaborative Governance in the development of Micro, Small and Medium Enterprises (MSMEs) in Kedungbanteng District, Banyumas Regency. Collaborative Governance involves various stakeholders, including government, the private sector, and civil society, to create comprehensive and sustainable solutions. Data from the Banyumas Regency Department of Manpower, Cooperatives and Small and Medium Enterprises shows a significant increase in the number of MSMEs from 2017 to 2021, with micro MSMEs dominating in Kedungbanteng District. This research highlights the important role of the Department of Manpower, Cooperatives and Small and Medium Enterprises (Dinnakerkop) and Bank Indonesia in supporting MSMEs. Bank Indonesia supports access to financing and digitalization, while Dinnakerkop provides training and strengthens the capacity of MSMEs. Collaboration with the private sector, such as ASPIKMAS, is also important. The successful example from Banyuwangi Regency shows that Collaborative Governance can increase the competitiveness of MSMEs through innovation and wider market access. This research aims to find out how effective and sustainable the collaboration process is in developing MSMEs in Kedungbanteng District to improve the performance and competitiveness of MSMEs